Basic Design of Anticlimber in Jabodebek Light Rail Transit - Sanjaya Wahyuningrum - Nim: 13114078, Ratih
Crashworthiness is the ability of a structure and its components to protect passengers during an accident. One of the crashworthiness component is anticlimber. Anticlimber prevents overriding by holding vertical force during collision by locking underframes. The main objective of this study is to perform preliminary design an anticlimber for Jabodebek Light Rail Transit. The anticlimber is designed using aluminum 6005A T5 material. Static tests of the anticlimber components are then performed with ANSYS software to find out the structural integrity of the anticlimber when loaded with vertical and longitudinal forces during collisions. The results obtained are that the anticlimber design successfully resists forces during collisions with a safety factor of 2.03. Dynamic simulation is carried out at speeds of 10 m/s and 20 m/s at 40 mm offset. The simulation results show that using anticlimber, the vertical displacement of the wheel is 32.32 mm at speed of 10 m/s and 88.43 mm at speed of 20 m/s. The vertical displacement of the wheel at both test speeds are still not allowed according to BS EN 15227: 2008 standard.